The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1163/092050611x581516
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose: Long-Term Biocompatibility Studies

Abstract: The bacterial cellulose (BC) secreted by Gluconacetobacter xylinus is a network of pure cellulose nanofibres which has high crystallinity, wettability and mechanical strength. These characteristics make BC an excellent material for tissue-engineering constructs, noteworthy for artificial vascular grafts. In this work, the in vivo biocompatibility of BC membranes produced by two G. xylinus strains was analyzed through histological analysis of long-term subcutaneous implants in the mice. The BC implants caused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 42 publications
2
65
0
Order By: Relevance
“…The potential toxicity of BC has been studied using BC nanofibers obtained by chemical and/or mechanical treatment of BC membranes in in vivo and in vitro experimental setups. Subcutaneous implantation of these BC nanofibers in BALB/c mice did not change the normal development of the animals; no differences were noted in histological analyses of the internal organs between implanted and control animals (Pertile et al, 2011). No toxicity in the liver and kidney organs of SD rats was observed when the rat model was used to study the efficiency of BC wound dressings (Kwak et al, 2015).…”
Section: Biocompatibility Of Bacterial Cellulosementioning
confidence: 93%
“…The potential toxicity of BC has been studied using BC nanofibers obtained by chemical and/or mechanical treatment of BC membranes in in vivo and in vitro experimental setups. Subcutaneous implantation of these BC nanofibers in BALB/c mice did not change the normal development of the animals; no differences were noted in histological analyses of the internal organs between implanted and control animals (Pertile et al, 2011). No toxicity in the liver and kidney organs of SD rats was observed when the rat model was used to study the efficiency of BC wound dressings (Kwak et al, 2015).…”
Section: Biocompatibility Of Bacterial Cellulosementioning
confidence: 93%
“…Cellulose has previously been employed as a permeable dialysis membrane and as diffusion limiting membranes within biosensors[24]. As well, previous studies found that cellulose produced by bacteria could support the proliferation of mammalian cells [20], [25], [26]. Synthetically produced cellulose scaffolds have also been employed for 3D mammalian cell culture [2], [19], [21], [23].…”
Section: Introductionmentioning
confidence: 99%
“…For such cases, the field of tissue engineering (TE) provides a promising potential alternative therapy to the conventional and complex surgical reconstruction of auricular cartilage by using ear-shaped autologous costal and nasoseptal cartilage [1][2][3]. Bacterial nanocellulose (BNC), a novel biomaterial with excellent biocompatibility and remarkable tissue integration capability [4][5][6][7][8], has been evaluated for several TE strategies and has shown to support adhesion, proliferation and differentiation of different cell types [9][10][11][12][13][14][15]. BNC is a natural biopolymer synthesized by various bacteria species, particularly Gluconacetobacter xylinus [16,17].…”
Section: Introductionmentioning
confidence: 99%